Women’s childhood experience and attachment to recreational parks in the Klang Valley, Malaysia - Khairrussalleh, Nadzirah (2018)
Women’s experience in childhood is important to determine the attachment to the recreational parks and urban green spaces in adulthood. Women’s roles and responsibilities had limits their participation in the leisure and recreational activities, thus decrease their attachment to recreational parks. Studies have shown that the adult frequency of visiting recreational park is correlated with the frequent visit during their childhood. However, studies on the women’s childhood experience and meaning of attachment to recreational parks were scarce. The aim of this study was to investigate how women from three main races in Malaysia which are Malay, Chinese, and Indian use and attach to recreational parks based on their childhood experience in nature. All data were collected by using the method of quota sampling which involved questionnaires distributed to 510 of respondents from two study sites: Bukit Kiara and Bukit Jalil Recreational Parks. The results show that there was a significant relationship between the women’s with positive childhood experience in nature and the frequency of visiting recreational parks in adulthood. Besides, the women who had lived in the rural area attached more to the recreational parks in adulthood. This study also found that Chinese were the majority of numbers of visitors at both parks followed by Malay and Indian. The findings will give implications towards increasing the women’s use of recreational parks by fulfilling the women’s needs and demands towards recreational parks and green spaces thus add new knowledge to the women’s use, childhood experience and meaning of attachment to the recreational parks in the Malaysian context, particularly in the Klang Valley area. Besides, add value to the women’s health and quality of life and well-being.